The Impact of Greenwashing Practices on Stock Liquidity and Volatility in Indonesia - Melvien Deisie Christin Welang; Juli Hendri; Sung Suk Kim (Universitas Pelita Harapan, 2025)
This study examines the impact of greenwashing on stock liquidity and volatility, using data from companies listed on the Indonesian stock exchange in the period 2018 to 2022. The results show that greenwashing has a positive impact on liquidity. The results show that greenwashing has a positive effect with stock price volatility, which indicates that increased greenwashing leads to higher market uncertainty. Furthermore, greenwashing has a negative effect on liquidity during the Covid-19 pandemic, but the effect of greenwashing on stock volatility is not different during the Covid-19 period.